Analysis of the Effect of Government Expenditure, Government Revenue, Money Supply and Interest Rates on Indonesia's Economic Growth - Simbolon, Richwan Gunawan; Hermanto, Bambang Agoes (Journal of Finance and Business Digital, 2024)
The objective of this study is to analyze the impact of government expenditure, government revenue, money supply, and interest rates on Indonesia's economic growth during the period 1990-2023. This research utilizes secondary data obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The analytical technique employed in this study is the Error Correction Model (ECM). The dependent variable in this research is economic growth, while the independent variables include government expenditure, government revenue, money supply, and interest rates. The findings reveal that the variables significantly affecting Indonesia's economic growth in the long and short term are government revenue, government expenditure, and interest rates. Therefore, it is crucial to adjust policies regulating government expenditure, interest rates, and government revenue to promote economic development.